Conscientious Refusal: A Workshop to Promote Reflective and Active Learning of Ethics, Communication Skills and Professionalism - Carla Lupi; Monica Broome; Aliye Runyan; Nicolette Schreiber (Association of American Medical Colleges, 2012)
Abstract Introduction This workshop was designed as an instructional tool to foster development of the nondirective pregnancy options counseling competency, a competency identified as a "does" level for third-year medical students by the Association of Professors of Gynecology and Obstetrics in the ninth edition of its curricular objectives. Methods The workshop consists of three modules that may be conducted independently or in combination with small or intermediate-sized groups of medical students. All the modules use challenging reproductive health scenarios as case material. The first module begins with two short trigger videos followed by structured discussion to provide an introduction to the core ethical issue of conscientious refusal, the limits of conscientious refusal in providing quality health care, and the connection between ethical breaches and errors in communication skills. The second module consists of a private values clarification exercise that may be further augmented with discussion. The third module uses the "helping trios role-play" technique to allow learners to practice the handling of ethical conflict with patients seeking objectionable medical interventions. Results The workshop was used in our obstetrics and gynecology clerkship over 3 academic years with more than 300 students. In anonymous pre- and postworkshop questionnaires with 140 students, participants reported heightened self-awareness after participation, with 95% rating the exercise as educationally valuable and 84% reporting that they would approach patient care situations differently in the future as a result. Data showed improvement in some parameters of options counseling competency and overall improvement in verbal and nonverbal communication skills. Discussion This 3 part session is intended to teach the ethical reasoning for professional handling of conscientious refusal and prepare students to maintain professionalism when finding themselves with ethical objection to a medical intervention that a patient requests or may need. Facilitators should be versed in patient centered communication and the American College of Obstetricians and Gynecologists Ethics committee opinion, competent in small and/or intermediate sized group facilitation skills, and facilitation of helping trios (for part 3 only.) Each part may stand alone as a separate exercise and/or small group discussion.